Effect of platelet-rich plasma on fibroblasts induced by lipopolysaccharide: in vitro study for wound healing - Idris, Muthoharoh; Kusuma, Indra; Juniarti, Juniarti (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2024)
Platelet-rich plasma (PRP) is expected to be an alternative therapy in wound healing by accelerating the inflammatory process and increasing the healing factors so that the healing process or inflammation is faster. The purpose of this study was to examine the effect of calcium chloride (CaCl2)-activated PRP on the viability, migration, and cytokine levels of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) of dermal fibroblast cells in lipopolysaccharide (LPS)-induced inflammatory conditions, as a model in wound healing in vitro. Fibroblast cells were grown in DMEM medium induced with LPS, and then CaCl2-activated PRP treatment was added. Measure fibroblast cell viability using CCK-8 kit (cell counting kit-8) was evaluated using a microplate reader, and the cell migration was evaluated using scratch-assay and TScratch software. Expression of IL-6 and VEGF using ELISA kit. All data were analyzed using software SPSS version 26 by performing a one-way analysis of variance (ANOVA), Kruskal Wills, and Mann-Whitney tests. The results showed that PRP significantly increased fibroblast cell viability in the 10% PRP treatment group. This study shows that PRP does not reduce IL-6 cytokine levels but can increase VEGF growth factor in fibroblast cell cultures. PRP increased cell migration so that the healing process was faster. In conclusion, the CaCl2-activated PRP on LPS-induced fibroblast cells can increase viability and accelerate cell migration; it can’t decrease IL-6 but can increase VEGF expression. PRP is expected to be an alternative therapy in wound healing.